Computer Simulation and Investigations of the Roof Mount Photovoltaic System - Sapundzhi, Fatima (International Journal of Online and Biomedical Engineering (iJOE), 2019)
The interest in the renewable energy sources is increasing due to the depletion of the conventional energy sources and the environmental pollution. In this paper we present a computer simulation and investigations of the roof mounted photovoltaic system. The results of the generated power of the 5kW built-in photovoltaic system by months over a period of 5 years are presented. Depending on the meteorological conditions, the investigated photovoltaic system generates year-round energy necessary for the needs of the household